Pembangunan Sistem Informasi Surat Perjalanan Dinas Berbasis Website - Nugroho Purnomo Aji; Ibnu Santoso (Politeknik Statistika STIS, 2022)
Official travel is a trip made by an employee of an agency related to official work assignments. During an official trip, it is necessary to make an assignment order and an official travel letter which aims to be an introduction when an employee carries out official travel activities within or outside the city. Currently, there are still some obstacles in the preparation and storage of data related to official travel letters at the Sragen BPS Regency, such as the length of time it takes to make letters, there is no recording and storage of data related to letters and report files, and there is no recapitulation of official travel expenses. This causes the preparation of accountability reports related to official travel to be constrained. Based on these problems, an information system that is integrated with the database is created. So that the creation, recording, and storage of data related to official travel letters is well organized. Based on the results of the Software Requirements Specification (SRS), a system is created that can create and record related letter data and there is a total cost recap. The system has been created and tested using the black box testing method, showing that all the functions on the system are running well. The average time needed to make a letter of assignment is 50.24 out of 10 trials. The score of the SUS test results obtained is 83.5 which indicates the system can function properly.